Assessment Of Cl 2 /CHF 3 Mixture For Plasma Etching Process On Barc And Tin Layer For 0.21 µm Metal Line: Silterra Case Study - et. al., Wan Faizal Mohamed-Hassan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In wafer fabrication manufacturing, aluminum etching process is a dry plasma etching process used as main process for construction of aluminum (Al) interconnects structures. As customer requirement changed for faster, more reliable and lower cost chips, chip manufacturers have learned to reduce the size of component on a chip in order to achieve those requirements(Ibrahim, Chik, & Hashim, 2016). As the geometry of the chip getting smaller, the width of Al line wiring specification also shrinking. To print the smaller geometry pattern requirement, the thickness in masking process also has to be reduced for better resolution. Such a thinner resist will create a challenge during plasma etching to ensure a minimal resist loss process which required new type of equipment but this research insist to sustain similar equipment. The use of oxide film as a hard mask has been evaluated by other researchers but alternative approach still needed to suit specific requirement of semiconductor factory installation base. This approach does require a process integration change and require a full technology qualification and easily take a lengthy qualification procedures especially when to qualify the existing products. It is worth trying at the situation of no other solution available. The challenge of insufficient margin for the metal line etching process for 0.2 µm width has caused the deformed metal pattern formation. This chemistry study of Cl2/CHF3 as a replacement gas to existing Cl2/O2 to address Organic backside anti refractive coating (OBARC) was evaluated and proven novelty where detail discussed in the following content.